Super 13Cr stainless steel metallographic etchant and corrosion method

By using metallographic corrosion liquid composed of iron chloride, concentrated hydrochloric acid, hydrofluoric acid, anhydrous ethanol and deionized water, the corrosion rate of existing metallographic corrosion liquids is solved, and the corrosion effect of clear corrosion of super 13Cr stainless steel is achieved, and the corrosion effect of safe and easy storage is achieved.

CN119913514APending Publication Date: 2025-05-02CHINA NATIONAL OFFSHORE OIL (CHINA) CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311429824.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-31
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

When the existing metallographic corrosion liquid corrode corrosion super 13Cr stainless steel, the corrosion rate is too fast and difficult to control, causing the inclusions on the surface of the sample to fall off and black spots, affecting observation, and is too volatile, causing personal harm and storage difficulties.

Method used

A metallographic corrosion solution consisting of ferric chloride, concentrated hydrochloric acid, hydrofluoric acid, anhydrous ethanol and deionized water is used to adjust the composition and reaction conditions to weaken the corrosion properties of the solution and control the corrosion rate, making it slower and easier to control.

Benefits of technology

It realizes clear corrosion of Super 13Cr stainless steel, reveals metallographic structure and grain boundaries, which are convenient for measurement and analysis, while reducing the harm to the experimenter, and the corrosion liquid is easy to store and recycle.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119913514A_ABST
    Figure CN119913514A_ABST
Patent Text Reader

Abstract

The invention discloses a super 13Cr stainless steel metallographic etchant and a corrosion method. The super 13Cr stainless steel metallographic etchant is composed of 4-6 g of ferric chloride, 10-20 mL of concentrated hydrochloric acid, 5-10 mL of hydrofluoric acid, 40-50 mL of absolute ethyl alcohol and 0-40 mL of water, the amount of the water is not zero, and the mass fraction of the concentrated hydrochloric acid is 36%-38%. The super 13Cr stainless steel metallographic etchant is prepared from ferric chloride, hydrochloric acid, hydrofluoric acid, absolute ethyl alcohol and deionized water, the raw materials are convenient to purchase, the etchant is easy to store, meanwhile, no obvious acid mist is generated, and harm to experimenters is reduced; the metallographic corrosive liquid can clearly corrode the metallographic structure of the super 13Cr stainless steel, the crystal boundary is obvious, the crystal grains are complete, when hydrofluoric acid and ferric chloride react to form fluoroferric acid, under the condition that hydrochloric acid is added, the corrosivity of the solution is weakened, the corrosion speed can be slowed down, the over-corrosion phenomenon is prevented, and the corrosion speed is easy to control.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a super 13Cr stainless steel metallographic etching liquid and a etching method, belonging to the technical field of alloy metallographic analysis. Background Art

[0002] With the development of oil and gas field exploitation in my country, the oil industry has been unable to meet the increasingly harsh and complex underground mining environment with ordinary material oil casing. Therefore, high-grade and high-strength corrosion-resistant steel oil casing has gradually been used in major oil field exploitation. Among them, super 13Cr stainless steel is a material with excellent corrosion resistance and has strong corrosion resistance in harsh working conditions. The addition of Cr elements to super 13Cr stainless steel not only improves the resistance to CO2 uniform corrosion, but also the Ni, Mo and other elements contained in 13Cr stainless steel can improve the material's stress corrosion cracking (SCC) and local corrosion resistance. Studies have shown that super 13Cr stainless steel is a martensitic stainless steel with good corrosion resistance. It has higher strength than ordinary 13Cr stainless steel, and has better low-temperature toughness and corrosion resistance. The C content is reduced and the precipitation of carbides is inhibited.

[0003] For example, 904L super 13Cr stainless steel is an alloy with Cr and Ni as the main strengthening elements. It is a low-carbon, high-nickel, molybdenum austenitic stainless acid-resistant steel with good activation-passivation transformation ability and excellent corrosion resistance. It has good corrosion resistance in non-oxidizing acids such as sulfuric acid, acetic acid, formic acid, and phosphoric acid, and has good pitting resistance in neutral chloride ion media. It also has good resistance to crevice corrosion and stress corrosion. It is suitable for sulfuric acid environments of various concentrations below 70°C, and is resistant to acetic acid of any concentration and any temperature under normal pressure, as well as mixed acid of formic acid and acetic acid, and its corrosion resistance is also very good. 904L super 13Cr stainless steel is mostly used in petroleum and petrochemical equipment, such as reactors in petrochemical equipment, and sulfuric acid storage and transportation equipment, such as heat exchangers.

[0004] In view of the excellent corrosion resistance of super 13Cr stainless steel represented by 904L, we must use appropriate metallographic etching liquid to etch out clear metallographic structure and complete grain boundaries, and analyze and measure them to judge product quality, and then improve and develop better stainless steel products. Through research and consultation, the most widely used metallographic etching liquids are aqua regia and ferric chloride hydrochloric acid aqueous solution; using these etching liquids for corrosion has poor corrosion effect, which can easily cause inclusions on the surface of the sample to fall off and black spots to appear, affecting later observation, and the volatile etching liquid is easy to cause personal injury and is not easy to store.

[0005] Traditional metallographic etching liquid has a very fast corrosion rate, and personnel need to accurately control the corrosion time. Based on the above problems, in order to prevent excessive corrosion without affecting the corrosion effect, it is necessary to provide an easy-to-control super 13Cr stainless steel metallographic etching liquid. Summary of the invention

[0006] The purpose of the present invention is to provide a super 13Cr stainless steel metallographic etching liquid with good corrosion effect and easily controllable corrosion speed, and further provide a super 13Cr stainless steel corrosion method, which can clearly etch the metallographic structure of the super 13Cr stainless steel, with obvious grain boundaries, convenient for measuring grain size and grain size, slow corrosion process, and easy to control speed.

[0007] The composition of the super 13Cr stainless steel metallographic etching solution provided by the present invention is as follows:

[0008] 4-6 g of ferric chloride, 10-20 mL of concentrated hydrochloric acid, 5-10 mL of hydrofluoric acid, 40-50 mL of anhydrous ethanol and 0-40 mL of water, wherein the amount of water is not zero;

[0009] Preferably: 5 g of ferric chloride, 15 mL of concentrated hydrochloric acid, 5 mL of hydrofluoric acid, 40 mL of anhydrous ethanol and 30 mL of water.

[0010] Preferably, the mass fraction of the concentrated hydrochloric acid is 36% to 38%.

[0011] Preferably, the mass fraction of the hydrofluoric acid is 40%.

[0012] Preferably, the purity of the anhydrous ethanol is ≥99.5%.

[0013] The metallographic etching liquid of the invention has simple composition, is easy to prepare and recycle, can be placed for a long time, will not deteriorate, and is easy to store.

[0014] Based on the metallographic etching solution, the present invention also provides a super 13Cr stainless steel corrosion method, comprising the following steps:

[0015] S1. Use sandpaper to polish the super 13Cr stainless steel metallographic specimen until there are no obvious scratches on the surface;

[0016] S2, grinding and polishing the super 13Cr stainless steel metallographic sample processed in step S1 by using a metallographic polishing machine;

[0017] S3, placing the super 13Cr stainless steel metallographic sample processed in step S2 in the metallographic etching solution for etching, that is, etching the super 13Cr stainless steel metallographic sample.

[0018] In the above-mentioned etching method, in step S1, at least one of 200-2000 mesh sandpaper is used for grinding, such as 200 mesh, 600 mesh, 800 mesh, 1000 mesh, 1200 mesh, 1500 mesh, and 2000 mesh water-abrasive sandpaper is used for grinding in sequence.

[0019] In the above-mentioned etching method, in step S2, a diamond spray polishing agent with a particle size of 2.5 um is used for grinding and polishing.

[0020] In the above-mentioned corrosion method, in step S3, the corrosion time is 2 to 6 minutes.

[0021] In the above-mentioned corrosion method, in step S3, after the corrosion is completed, the method further comprises the steps of washing the super 13Cr stainless steel metallographic sample with water and anhydrous ethanol in sequence.

[0022] The super 13Cr stainless steel metallographic etching liquid of the invention is prepared from ferric chloride, hydrochloric acid, hydrofluoric acid, anhydrous ethanol and deionized water, the raw materials are convenient to purchase, the etching liquid is easy to store, and no obvious acid mist is generated, thereby reducing the harm to experimenters; the metallographic etching liquid of the invention can clearly etch out the metallographic structure of the super 13Cr stainless steel, and the grain boundary is obvious and the grains are complete; when hydrofluoric acid and ferric chloride react to form fluoroferric acid, hydrochloric acid is added to weaken the corrosiveness of the solution, slow down the corrosion rate, prevent the over-corrosion phenomenon, and make the corrosion rate easy to control. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The present invention is a schematic diagram of the process of preparing the metallographic etching solution and the etching method.

[0024] Figure 2 This is a metallographic structure photograph of the sample after being corroded by the metallographic etching solution prepared in Example 1 of the present invention.

[0025] Figure 3 and Figure 5 All of them are metallographic photos of the samples after being corroded by ferric chloride hydrochloric acid aqueous solution.

[0026] Figure 4 This is a metallographic structure photograph of the sample after being corroded by the metallographic etching solution prepared in Example 2 of the present invention. DETAILED DESCRIPTION

[0027] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.

[0028] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0029] Example 1: Preparation of super 13Cr stainless steel metallographic etching solution and corrosion of super 13Cr stainless steel

[0030] 1. Preparation of super 13Cr stainless steel metallographic etching solution

[0031] like Figure 1 As shown, the metallographic etching solution of this embodiment is prepared from ferric chloride, concentrated hydrochloric acid, hydrofluoric acid, anhydrous ethanol and deionized water, and the process is as follows:

[0032] Use an electronic balance to weigh 5 g of ferric chloride, 15 mL of concentrated hydrochloric acid, 5 mL of hydrofluoric acid, 40 mL of anhydrous ethanol and 30 mL of deionized water to prepare a solution.

[0033] Among them, the purity of ferric chloride is ≥99%, the mass fraction of concentrated hydrochloric acid is 37%, the mass fraction of hydrofluoric acid is about 40%, and the purity of anhydrous ethanol is ≥99.5%.

[0034] 2. Corrosion of super 13Cr stainless steel metallographic structure

[0035] The corrosion steps are as follows Figure 1 shown.

[0036] The metallographic specimens of super 13Cr stainless steel of suitable size are polished with 200 mesh, 600 mesh, 800 mesh, 1000 mesh, 1200 mesh, 1500 mesh and 2000 mesh water-abrasive sandpaper in turn; after each grinding of sandpaper of one mesh, the metallographic specimen is rotated 90 degrees in parallel to be polished on the sandpaper of the next mesh, so as to ensure that the wear marks on the sandpaper of the next mesh can cover the wear marks on the sandpaper of the previous mesh each time. Then, a 2.5um diamond spray polishing agent is used for polishing until the surface is as bright as a mirror. The polished metallographic specimen is immersed in the above-prepared metallographic etching liquid, so that the etching liquid immerses the surface of the metallographic specimen, and the metallographic specimen is corroded for about 3 minutes. The surface of the metallographic specimen loses its luster and becomes gray. The metallographic specimen is quickly taken out, first washed with deionized water, then rinsed with anhydrous ethanol, and finally the corroded surface is blown dry to complete the corrosion of the metallographic specimen.

[0037] The metallographic structure of the sample after being etched by the metallographic etching solution prepared in this embodiment is shown in FIG. Figure 2 shown.

[0038] According to the above-mentioned etching method, the metallographic etching solution was replaced with ferric chloride hydrochloric acid aqueous solution (ferric chloride 10g, concentrated hydrochloric acid 30mL, deionized water 120mL). The metallographic structure photo of the sample after etching is as follows: Figure 3 shown.

[0039] contrast Figure 2 and Figure 3It can be seen that the metallographic structure presented by the etching solution of the present invention is clearer and the etching effect is better. Specifically, the traditional super 13Cr stainless steel metallographic etching solution will cause the polished surface to turn black and the structure to be over-corroded after etching for 1 minute; when the metallographic etching solution of the present invention is used for etching for 3 minutes, the polished surface will turn gray and the grain boundary and structure will be visible.

[0040] In summary, the conventional super 13Cr stainless steel metallographic etching solution (without hydrofluoric acid) over-corrodes the structure, the grain boundaries are not obvious, and it is difficult to distinguish the structure and orientation; after the metallographic etching solution of the present invention is used for etching, the structure is obvious and the grain boundaries are clear.

[0041] Example 2: Preparation of metallographic etching solution for super 13Cr martensitic stainless steel and corrosion of super 13Cr martensitic stainless steel

[0042] 1. Preparation of metallographic etching solution for super 13Cr martensitic stainless steel

[0043] like Figure 1 As shown, the metallographic etching solution of this embodiment is prepared from ferric chloride, concentrated hydrochloric acid, hydrofluoric acid, anhydrous ethanol and deionized water, and the steps are as follows:

[0044] Use an electronic balance to weigh 6 g of ferric chloride, 20 mL of concentrated hydrochloric acid, 10 mL of hydrofluoric acid, 50 mL of anhydrous ethanol and 40 mL of deionized water to prepare a super 13Cr martensitic stainless steel metallographic corrosion solution.

[0045] Among them, the purity of ferric chloride is ≥99%, the mass fraction of concentrated hydrochloric acid is 37%, the mass fraction of hydrofluoric acid is about 40%, and the purity of anhydrous ethanol is ≥99.5%.

[0046] 2. Corrosion of metallographic structure of super 13Cr martensitic stainless steel

[0047] The corrosion steps are as follows Figure 1 shown.

[0048] The longitudinal section of the super 13Cr martensitic stainless steel metallographic specimen with a size of 12mm*10mm*12mm is polished with 200 mesh, 600 mesh, 800 mesh, 1000 mesh, 1200 mesh, 1500 mesh, and 2000 mesh sandpaper in turn; after each polishing with a mesh sandpaper, the metallographic specimen is rotated 90 degrees in parallel and polished on the next mesh sandpaper to ensure that the wear marks on the next mesh sandpaper can cover the wear marks on the previous mesh sandpaper. Then it is polished with a 2.5um diamond spray polishing agent until the surface of the specimen is as bright as a mirror. The polished metallographic specimen is immersed in the above-prepared metallographic etching liquid, so that the etching liquid immerses the surface of the metallographic specimen. After etching for about 3 minutes, the surface of the metallographic specimen loses its luster and becomes gray. The metallographic specimen is quickly taken out, first washed with deionized water, then rinsed with anhydrous ethanol, and finally blown dry. The corrosion surface is completed.

[0049] The metallographic structure of the sample after being etched by the metallographic etching solution prepared in this embodiment is shown in FIG. Figure 4 shown.

[0050] According to the above-mentioned etching method, the metallographic etching solution of the present invention is replaced with an aqueous solution of ferric chloride hydrochloric acid (10 g of ferric chloride, 30 mL of concentrated hydrochloric acid, and 120 mL of deionized water). The metallographic structure photograph of the sample after etching is as follows: Figure 5 shown.

[0051] contrast Figure 4 and Figure 5 It can be seen that the metallographic structure presented by the etching solution of the present invention is clearer, the grain boundaries are more obvious, and the etching effect is more excellent. Specifically, the traditional super 13Cr stainless steel metallographic etching solution, the polished surface is blackened and the structure is over-corroded after etching for 1 minute; when the metallographic etching solution of the present invention is used for etching for 3 minutes, the polished surface is gray, and the grain boundaries and structure are clearly visible.

[0052] In summary, the conventional super 13Cr stainless steel metallographic etching solution (without hydrofluoric acid and with poor concentration ratio) over-corrodes the structure, the grain boundaries are not obvious, and it is difficult to distinguish the structure and orientation; after being corroded by the metallographic etching solution of the present invention, the structure is obvious and the grain boundaries are clear.

Claims

1. A super 13Cr stainless steel metallographic etching solution, the composition of which is as follows: 4-6 g of ferric chloride, 10-20 mL of concentrated hydrochloric acid, 5-10 mL of hydrofluoric acid, 40-50 mL of anhydrous ethanol and 0-40 mL of water, wherein the amount of water is not zero.

2. The metallographic etching solution according to claim 1, characterized in that: The mass fraction of the concentrated hydrochloric acid is 36% to 38%.

3. The metallographic etching solution according to claim 1 or 2, characterized in that: The mass fraction of the hydrofluoric acid is 40%.

4. The metallographic etching solution according to any one of claims 1 to 3, characterized in that: The purity of the anhydrous ethanol is ≥99.5%.

5. A corrosion method for super 13Cr stainless steel, comprising the following steps: S1. Use sandpaper to polish the super 13Cr stainless steel metallographic specimen until there are no obvious scratches on the surface; S2, grinding and polishing the super 13Cr stainless steel metallographic sample processed in step S1; S3, placing the super 13Cr stainless steel metallographic sample processed in step S2 in the metallographic etching solution of any one of claims 1 to 4 for etching, that is, achieving corrosion of the super 13Cr stainless steel metallographic sample.

6. The etching method according to claim 5, characterized in that: In step S1, at least one of sandpapers with mesh sizes of 200-2000 is used for grinding.

7. The etching method according to claim 5 or 6, characterized in that: In step S2, a diamond spray polishing agent with a particle size of 2.5 um is used for polishing.

8. The etching method according to any one of claims 5 to 7, characterized in that: In step S3, the erosion time is 2 to 6 minutes.

9. The etching method according to any one of claims 5 to 8, characterized in that: In step S3, after the corrosion is completed, the super 13Cr stainless steel metallographic sample is washed with water and then with anhydrous ethanol in sequence.